Investigation of physical and chemical properties of new derivatives of 5-(thiophene-3-ylmethyl)-4R-1,2,4-triazole-3-thiols - A. V. Khilkovets (Zaporozhye State Medical University, 2021)
Heterocyclic compounds are one of the most important branches of modern organic chemistry and are widely used in medicine, pharmacy, agriculture, and in the production of new materials. One of these compounds is 1,2,4-triazole, which has attracted the attention of scientists around the world for many years. The aim of the work is to synthesize new derivatives of 5-(thiophene-3-ylmethyl)-4R-1,2,4-triazole-3-thiols and study their physical-chemical properties, conducting primary pharmacological screening. Materials and methods. Organic synthesis classical methods were used in the study, as well as a complex of physical-chemical analysis methods (1H NMR spectroscopy, elemental analysis, Elisa and chromato-mass spectral studies) were done. Prediction of pharmacological activity was carried out by using the PASS online computer program. Results. Two initial compounds were obtained: 5-(thiophene-3-ylmethyl)-4phenyl-1,2,4-triazole-3-thiol and 5-(thiophene-3-ylmethyl)-4H-1,2,4-triazole-3-thiol. During their further chemical transformation, a number of new corresponding alkyl derivatives were obtained. The structure of the synthesized compounds was confirmed using modern physical-chemical methods of analysis. Based on the results of pharmacological screening, the high activity of the obtained compounds can be predicted. Conclusions. 5-(thiophene-3-ylmethyl)-4H-1,2,4-triazole-3-thiol, 5-(thiophene-3-ylmethyl)-4-phenyl-1,2,4-triazole-3-thiol and a number of their alkyl derivatives were synthesized. The structure and individuality were proved thanks to modern physical and chemical methods of analysis. Having analyzed the results of primary pharmacological screening of a number of obtained compounds, some of them were selected for further study.